Statistical inference for type I multiply left-censored samples from Weibull distribution - Fusek, M.; Michalek, J. (Кибернетика и системный анализ, 2019)
Left-censored data with one or more detection limits occur frequently in many application areas. In this paper, the computational procedure for calculation of maximum likelihood estimates of the parameters for type I multiply left-censored data from underlying Weibull distribution is suggested and used considering various numbers of detection limits. The expected Fisher information matrix is analytically determined and its performance is compared with sample (observed) Fisher information matrix using simulations. Simulations are focused primarily on the properties of estimators for small sample sizes. Real data illustration is included.